Meningkatkan Kemandirian Emosi dan Sosial Remaja Pengguna Narkoba Melalui Program Konseling Sebaya di Pengajian Mingguan: Studi di PAC IPNU-IPPNU Wuluhan Jember - Muhammad Muhib Alwi; Maskud Maskud (LP2M UIN Kiai Haji Achmad Siddiq Jember, 2018)
Problems that arise in adolescence include: problems related to physical and motor development, problems related to the development of social behavior, religious morality, and problems associated with the development of emotional personality. Unstable and uncontrollable emotional reactions and expressions during adolescence can have an impact on their personal and social life. Where teens feel depressed and withdrawn or actually behave aggressively. Today teenage life is so alarming. The behavior of free sex, drinking, drug abuse, antisocial, and brawl between gangs became their lifestyle. As happened in the district of Wuluhan Jember. Therefore it needs serious and thorough handling. One of the handling done is with peer counseling, where after peer counseling by the mentor of IPNU-IPPNU cadres for two months there is a significant changeof social independence. Where adolescent drug victims are more independent in the social attitude so have the courage to refuse the offer drugs.